Guidlines for the development of an HIV/AIDS workplace support programme for teachers - Ganyaza-Twalo, Thulisile (University of the Western Cape, 2013)
Philosophiae Doctor - PhD === The aim of this study was to develop guidelines for an HIV/AIDS support programme for teachers. In order to achieve this goal, Intervention Research: Design and Development model by Rothman and Thomas (1994) was adopted to guide the research process. Intervention research is a form of applied qualitative research utilized by researchers to design and develop interventions to ameliorate social problems. Intervention research: design and development model has six phases and unique operational steps to follow in each phase. The researcher adopted the first three phases to facilitate the design of the guidelines to assist with development of a programme to support teachers. Problem analysis and project planning is the first phase. In this phase, the aim was to understand the experiences of HIV/AIDS among teachers and in schools. Information was gathered from HIV/AIDS coordinators, principals, teachers living with HIV. === South Africa